Coyote Was Going There : Indian Literature of the Oregon Country - Ramsey, Jarold, 1937- (Book collections on Project MUSE., 1977)
The material cause of this book is a Central Oregon childhood spent around Indians and devoted to hunting for the artifacts of their ancestors, the efficient cause is in the works of the late Melville Jacobs.